ANALISIS KEMELEKAN SAINS (SCIENCE LITERACY) DAN KEMELEKAN INKUIRI (INQUIRY LITERACY) GURU MATA PELAJARAN IPA SMP - A. Wahab Jufri; Hikmawati Hikmawati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2014)
Abstrak: Kemelekan sains dan kemelekan inkuiri adalah dua hal penting yang harus dikuasai secara memadai oleh peserta didik dalam era globalisasi. Telah dilakukan penelitian dengan tujuan untuk menganalisis tingkat kemelekan sains dan kemelekan inkuiri guru-guru mata pelajaran IPA SMP. Sampel penelitian terdiri atas 25 orang guru IPA SMP yang sedang menempuh program S2 pada Program Studi Magister Pendidikan IPA di Universitas Mataram tahun akademik 2012/2013. Penelitian dilaksanakan dengan pola pretes-postes dan diberikan perlakuan berupa pelatihan berjenjang dengan total waktu 400 menit (4 kali tatap muka). Hasil penelitian menunjukkan bahwa tingkat kemelekan sains dan inkuiri guru-guru IPA SMP masih tergolong rendah. Dalam pola pelatihan berjenjang seperti ini guru hanya mampu meningkatkan kemelekan sains sebesar 1% dan kemelekan inkuiri sebesar 5%. Mengingat pentingnya peran kemelekan sains dan kemelekan inkuiri bagi peserta didik maka perlu dilakukan upaya sistematis untuk meningkatkan kompetensi profesional para guru khususnya aspek kemelekan sains dan kemelekan inkuiri.Kata kunci: kemelekan, sains, inkuiriÃÂ Abstract: Science literacy and inquiry literacy are two important aspects of life skills needed by both teachers and students in this globalization era. This research has been undertaken to analyzed science and inquiry literacy of high school science teachers in West Nusa Tenggara Provence. The research subjects consist of 25 teachers who joined the master degree inÃÂ the Magister Study Program of Educational Sciences in the University of Mataram during academic year 2012/2013. The research has been designed as one group pretest-postest experiment. The teacher students have been trained for 4 times of lecturer classes which equal to 400 minutes. The results of this research shown that the average scoresÃÂ of science literacy and inquiry literacy of those student teachers can be categorized as low level (M Ã¢â°Â¤ 50%). The average scores of science literacy increased only 0,7 % and the inquiry literacy score increased about 5% after the training. Due to the important of these aspects in the context of science, therefore it is strongly recommended to constructs systematic and continuous efforts to help improve the teachers professional competences includes the science literacy and inquiry literacy.Keywords: literacy, sience, inquiry